A STUDY ON INFLUENCE OF ENVIRONMENTAL WORKING CONDITIONS ON WEAR OF A BALL SCREW BASED ON TCVN7699-2-30 - Tran, Duc-Toan; Pham, Van-Hung; Le, Duc-Do; Bui, Tuan-Anh (Journal of Applied Engineering Science, 2022)
Ball screw in a key component of a machine that affects the performance, accuracy working condition, and lifetime of the machines. Temperature and relative humidity (RH) are two environmental factors that affect the assembly condition and lubrication between surfaces. The study proposed an experimental investigation of the influences of the specific environmental working conditions corresponding to the tropical climate and the Vietnamese standardization system TCVN7699-2-30 on wear of a ball screw with serial No. of PSS1505N1D0261. The results show that the ball screw working in the environmentally lubricated conditions according to the TCVN7699-2-30, the longevity increased by 4.18 times as compared to the ISO 3408-5. The fundamentals for calculation and adjustment of the environmental working conditions of the machines with a purpose of ensuring the most feasible operation accuracy of the machines should be recommended based on specific conditions.